Hotshot - Garwood, Julie (New York Dutton, 2013)
Inheriting a luxurious oceanfront resort under a condition that she must run it profitably for one year to claim full ownership, food critic Peyton Lockhart is targeted by dangerous rivals and is protected from a threat against her life by childhood friend and attractive FBI agent Finn MacBain
Keywords: United States. -- Federal Bureau of Investigation -- Officials and employees -- Fiction; Food writers -- Fiction; Resorts -- Management -- Fiction; Man-woman relationships -- Fiction